Comparative Assessment of Civil Procedure in Indonesia and The Netherlands: The Source of The Principles - Verdian, Vincentius (Jurist-Diction, 2025)
This paper assessed the different sources of principles in the civil procedure between Indonesia and the Netherlands. Indonesia still uses the Inlandsch Reglement (IR) and the Rechtsreglement voor de Buitengewesten (RBg) while the Netherlands has updated their Civil Code incorporating the principles from the European Convention on Human Rights (ECHR). Therefore, the outdated regulation used in Indonesia lacks procedural protections such as timely case resolution and affordable proceedings. This matter creates a legal uncertainty between the Indonesian Constitution, the International Covenant on Civil and Political Rights (ICCPR), which emphasizes Human Rights, and the old Code of Civil Procedure itself. Although the Indonesian Government already made some efforts to fix this problem, it remains insufficient. This paper suggests that to improve legal certainty in Indonesia, they are required to make a new Code of Civil Procedure with provisions that ensure efficient and affordable legal proceedings.